FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN IBU HAMIL TENTANG TANDA TANDA BAHAYA KEHAMILAN - Mariani, Mariani; Emma, Arrifah Noer; Chairunnisa, Chairunnisa (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Data from the Ministry of Health of the Republic of Indonesia (Kemenkes) in 2015 showed that of 100,000 live births in Indonesia, 305 of them ended in the death of the mother. The high maternal mortality rate (MMR) – 305/100,000 live births – prompted the government to carry out structural interventions; one of them is to include the target for reducing the MMR in the 2014-2019 National Medium-Term Development Plan (RPJMN). In the 2014-2019 RPJMN, the government targets a reduction in the MMR from 205/100,000 births to 276/100,000 live births. This study was to analyze the relationship between maternal age, education, and occupation with mother's knowledge of the danger signs of pregnancy at the Pelambuan Health Center. Methods: Cross sectional research design with Accidental Sampling technique. The study population was all pregnant women in the working area of the Pelambuan Health Center with a total of 359 people. Descriptive and statistical data analysis using chi-square test and multiple logistic regression test. The results of the chi-square test showed that there was a relationship between maternal age (0.001), parity (0.001), occupation (0.000), and knowledge of pregnant women. Results: Based on the results of the study, it is known that respondents with age at risk (<20 years ->35 years) are 26 respondents (80%). This number is more when compared to respondents who have a non-risk age (20-35 years) as many as 4 respondents (20%). The relationship between parity and knowledge of pregnant women about the danger signs of pregnancy showed that the respondents with the age at risk (<20 years ->35 years) were 52 respondents (80%). This number is more when compared to respondents who have a non-risk age (20-35 years) as many as 13 respondents (20%). This study has a relationship between the age of pregnant women and the knowledge of pregnant women in recognizing the danger signs of pregnancy in the Pelambuan Health Center Work Area because it is associated with a high risk of pregnancy, the risk of pregnancy arises because they are not ready psychologically or physically. Psychologically, generally adolescents aged < 21 years are not ready to become mothers, as a result, apart from being unprepared, their pregnancies are not well maintained. This unhealthy psychological condition can make contractions during labor not run smoothly so that the possibility of the delivery process will be risky.